Tiga Pilar Epistemologi Pesantren dalam Membentuk Otoritas Keilmuan dan Akhlak - Bisyarotul Masfufah; Muhammad Husni (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
The epistemology of Pesantren is based on the integration of three pillars of authority: Kiai (Personal), Kitab Kuning (Textual), and Meditation (Riyaḍah Ruḥiyyah/Spiritual), which serve as the foundation for shaping the academic and moral authority of the students (santri). Using a qualitative phenomenological approach and a study of classical literature (turas), the pesantren is viewed as a center for knowledge transmission that combines rational, textual, and spiritual dimensions, transcending its mere institutional function. The findings indicate that the Kiai functions as a living authority and the source of the chain of transmission (sanad/isnad) that guarantees the validity of knowledge and instills blessings (barakah). This complements the role of the Kitab Kuning as the textual authority that provides the framework for knowledge (istinbaṭ) through the sorogan (individual recitation) and bandongan (group study) traditions. What distinguishes this model is the role of Contemplation, which, through the practices of mujahadah (striving against one's base desires) and taṣfiyyah al-qalb (purification of the heart), acts as an internal-spiritual authority that purifies the soul, enabling the santri to achieve ma’rifat (intuitive knowledge) and internalize the values of wara’ (prudence/caution) and tawaḍu’ (humility). The synergistic integration of these three pillars produces the profile of a Scholar-Student (Ulama-Santri) with a dual authority: valid academic authority based on sanad and text, and strong moral authority based on spirituality and exemplary conduct. This unique epistemological model is highly relevant in facing the challenges of modernity, as it ensures that intellectual intelligence is balanced with spiritual integrity, producing graduates who are not only ’alim (knowledgeable/scholarly) but also ’amil (practicing/possessing noble character).